COMPETITION AS THE BASIS OF MARKET RELATIONS - HROMOVA, Olha; ABDULLAIEVA, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyses the category of "competition" and provides a classification of this concept by various features. The basic principles of formation and the mechanism of functioning of competitive potential are indicated. The article considers theoretical and methodical approaches with application of methods of analysis, which allow ensuring increase of competitiveness of an enterprise. There are 2 approaches to the concept of competition: - the economic approach, which is based on the fulfilment of two conditions: the presence in the market of a large number of independently acting buyers and sellers of any particular product or resource; freedom for buyers and sellers to enter or leave certain markets; - the socio-political approach, which interprets competition mainly from the standpoint of group (or class) confrontation or struggle. Competition is generally recognised as the basis for the development of market relations. Competition above the market takes different forms and is carried out by different methods. In this regard, it can be systematised according to a number of features. A firm’s position in an industry is determined by its competitive advantage. Ultimately, firms outperform their rivals if they have a strong competitive advantage. This advantage is achieved mainly through lower costs or product differentiation. Any strategy should pay attention to both types of competitive advantage, although strictly adhering to one of them. Another important variable that determines the strategy is the scope of competition, or the breadth of the goal that the firm is aiming for within its industry. The company must decide for itself how many types of goods it will produce, what channels it will use, and what range of customers it will serve. Depending on this, a strategy should be chosen. Consequently, competition between companies is becoming increasingly fierce. The manufacturer has the opportunity to win the competition. There are methods that allow you to outperform your rivals. Thus, in order to take a favourable position in the market, a firm must create a competitive advantage and then maintain it.